2003
DOI: 10.1002/macp.200350005
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Chain Transfer Copolymerization of Methyl Methacrylate and Butyl Acrylate

Abstract: In this work it is shown that catalytic chain transfer is a very efficient way of controlling molecular weight in the copolymerization of methyl methacrylate (MMA) and butyl acrylate (BA). The experimental data are compared to a previously developed model based on copolymerization kinetics and the mechanisms for catalytic chain transfer and for cobalt‐mediated living radical polymerization that can describe the observed transfer constants. Secondly, it is shown that the presence of a catalytic chain transfer a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 47 publications
1
22
0
Order By: Relevance
“…There are several publications dealing with Ni‐based ATRP in the literature, and a few Ni complexes have been found to be active, including [Ni{ o,o (CH 2 NMe) 2 C 6 H 3 }Br],9 NiBr 2 (PPh 3 ) 2 /Al(O‐ i ‐Pr) 3 ,10 NiBr 2 (PBu 3 ) 2 ,11 [Ni(CCPh) 2 (PBu 3 ) 2 ],13 tetrisethylthiuram disulfide/NiCl 2 /PPh 3 ,14 and others 14–21. Organocobalt porphyrin complexes and cobaltocene have been reported as catalysts in the quasi‐living radical polymerizations of acrylates and MMA, respectively 22–27. SnCl 2 and MA 5 ‐DETA together have been reported to act as a catalyst in the radical polymerization of MMA.…”
Section: Resultsmentioning
confidence: 99%
“…There are several publications dealing with Ni‐based ATRP in the literature, and a few Ni complexes have been found to be active, including [Ni{ o,o (CH 2 NMe) 2 C 6 H 3 }Br],9 NiBr 2 (PPh 3 ) 2 /Al(O‐ i ‐Pr) 3 ,10 NiBr 2 (PBu 3 ) 2 ,11 [Ni(CCPh) 2 (PBu 3 ) 2 ],13 tetrisethylthiuram disulfide/NiCl 2 /PPh 3 ,14 and others 14–21. Organocobalt porphyrin complexes and cobaltocene have been reported as catalysts in the quasi‐living radical polymerizations of acrylates and MMA, respectively 22–27. SnCl 2 and MA 5 ‐DETA together have been reported to act as a catalyst in the radical polymerization of MMA.…”
Section: Resultsmentioning
confidence: 99%
“…In the early stage of polymerization, the copolymerization rate of BA and MMA were fast. Pierik and van Herk [24] have found that the reactivity ratios for BA and MMA were 0.395 and 2.28, respectively; besides, Wang and Pan [22] reported that their reactivity ratios were 0.47 and 2.17, indicating that BA-MMA copolymerization would be close to ideal copolymerization. From this point, the conversion rate of BA and MMA was relatively higher than AA initially, and stable latex particles could be formed.…”
Section: Effect Of Polymerization Process On Particle Size and Morphomentioning
confidence: 99%
“…Monomers such as the acrylates and styrene also undergo CCT, but their apparent chain transfer constants are much lower because of a lowering of the effective catalyst concentration due to Co-C bond formation. [6][7][8][9][10][11][12][13] Furthermore, the resulting vinyl end functionality is less reactive Summary: Macromonomers consisting of a butyl acrylate (BA) tail and a-methyl styrene (AMS) or benzyl methacrylate (BzMA) unsaturated termini were synthesized via catalytic chain transfer (CCT) polymerization employing the low spin bis(difluoroboryl)dimethylglyoximato cobalt (II) (COBF) complex. The structures of the generated macromonomers were characterized via 1 H and 13 C NMR spectroscopy and electrospray ionization mass spectrometry (ESI-MS).…”
Section: Introductionmentioning
confidence: 99%
“…The theory behind endgroup control in CCT polymerization has previously been discussed in great detail elsewhere [6,9,10,20 -22] and acrylate macro-monomers with methacrylate or AMSderived vinyl endgroups have been successfully prepared previously by Moad and co-workers. [23][24][25] For kinetic studies on the copolymerization of acrylates with methacrylates in the presence of a CCT agent we refer to the work by Pierik et al [9,10] Since it is unavoidable in a CCT copolymerization that some of the monomer designed to be only introduced as a vinyl endgroup are incorporated in the polymer backbone, it is important to investigate how many of these units are incorporated per chain and how effective the chain end functionalization is. The aim of the present paper is to investigate the use of CCT for the preparation of macromonomers of butyl acrylate (BA) and a-methyl styrene (AMS) as well as BA and benzyl methacrylate (BzMA) [26] and their subsequent analysis via size exclusion chromatography, 1 H and 13 C NMR spectroscopy [27] as well as electrospray ionization mass spectrometry (ESI-MS).…”
Section: Introductionmentioning
confidence: 99%